Preparation of bactericidal PDMS surfaces by benzophenone photo-initiated grafting of polynorbornenes functionalized with quaternary phosphonium or pyridinium groups - Lou, Yuzhen; Schapman, Damien; Mercier, Dimitri; Suer, N. Ceren; Eren, Tarik; Thebault, Pascal; Kebir, Nasreddine (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Cationic ROMP-polymers bearing ammonium or phosphonium groups were photo-grafted onto a PDMS surface via the thiol-ene click reaction, in the presence of benzophenone. The PDMS surface was first thiolated using pentaerythritol tetrakis (3-mercaptopropionate) (PTTMP) under UV, in the presence of benzophenone. The obtained cationic surfaces exhibited charge densities above 1014 charge/cm2 and a higher degree of hydrophilicity compared to non-grafted surfaces. The live and dead tests performed by fluorescence microscopy revealed an effective contact bactericidal effect of these surfaces against Escherichia coli and Staphylococcus epidermidis.
Keywords: Quaternary ammonium; ROMP; Photo; Grafting to PDMS; Bactericidal Thiol-ene; BLOCK-COPOLYMERS; STAPHYLOCOCCUS-AUREUS; POLY(ETHYLENE GLYCOL); SILICONE; POLY(DIMETHYLSILOXANE); ANTIBACTERIAL; FACILE; IMMOBILIZATION; POLYMERS; COATINGS; Polymer Science